Possibilities for Developing Flexible Employment Forms in Lithuania - Stankevičienė, Asta; Gruževskis, Boguslavas (Ekonomika, 2004)
The article reviews the concept of flexible employment forms and their effects on the labour market. It analyses foreign experience in application of flexible employment forms, discusses possibilities for assessment of the economic effect of the application of flexible employment forms in Lithuania and results of an expert survey.